1995
DOI: 10.1021/ac00110a027
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cytochrome c Variants with High-Resolution FTICR Mass Spectrometry: Correlation of Fragmentation and Structure

Abstract: The dissociation of cytochrome c ions (15+ charge state) generated by electrospray ionization has been studied by Fourier transform ion cyclotron resonance mass spectrometry (FTICR) using a sustained off-resonance irradiation/collision-induced dissociation (SORI-CID) technique. Over 95% of the fragment ions can be accurately assigned (to better than 10 ppm), yielding information on the primary sequences of the various proteins. Up to four stages of mass spectrometry (MS4) have been achieved without the need fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 63 publications
3
92
0
Order By: Relevance
“…Wu et al (1995) studied dissociation of the þ15 charge state of cytochrome c ions from different sources. SORI-CID results in numerous backbone cleavages of the proteins.…”
Section: Ms Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Wu et al (1995) studied dissociation of the þ15 charge state of cytochrome c ions from different sources. SORI-CID results in numerous backbone cleavages of the proteins.…”
Section: Ms Nmentioning
confidence: 99%
“…In this review, we will discuss only selected studies that demonstrate the utility of SORI-CID for examining structures and relative stabilities of proteins and protein-ligand complexes in the gas phase Wu et al, 1995;Liu et al, 1996;Wu et al, 1997;Gao et al, 1999). Fragmentation patterns obtained using SORI-CID are very sensitive to small changes in the primary structure of peptides and proteins.…”
Section: Structure Determinations Using Sori-cidmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to chemical probes of gas phase ion structure [1][2][3][4][5][6][7][8][9][10][11][12][13][14], a number physical methods are being developed to examine gas-phase peptide and protein ion structure [15][16][17][18][19][20][21][22][23][24][25][26][27], including collisional activation to examine fragmentation pathways [18 -23, 25-27]. A few studies have suggested that ion conformation may influence fragmentation pathways [19,23,27,28]. In this paper, we examine this issue for the fragmentation of a series of compact and elongated conformations of ubiquitin ions.…”
mentioning
confidence: 99%
“…To date, tandem mass spectrometry (MS/MS) of proteins, has been reported using several dissociation modes. [12][13][14][15][16][17][18] In the case of CA2, MS/MS analyses have been performed by Fourier transform ion cyclotron resonance mass spectrometry. 13,14) The product ions obtained in this study are consistent with these reports, and they were assigned accordingly.…”
Section: Product Ion Spectra Of a Xed Charge Number At DI Erent Ph Comentioning
confidence: 99%